Analisis Konten Promosi AIESEC Future Leaders : Studi pada Akun Instagram @aiesecupnvy - Nakita Ummi Fadhilah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe the characteristics of AIESEC Future Leaders (AFL) promotional content on the Instagram account @aiesecupnvy using a descriptive qualitative approach and Charles Sanders Peirce's semiotic analysis. Promotional content was chosen as the focus of the research because it plays a crucial role in building audience interest and understanding of the self-development programs offered. The research results indicate that AIESEC UPNVY utilizes several types of visual and verbal signs designed to attract attention and build emotional closeness with its target audience, namely students and young people. Content highlighting program benefits, testimonials from previous participants in the form of single words, expressions of delegates' happiness, and symbolic videos about togetherness proved effective in creating social proof and strengthening AFL's image as a program that provides valuable experiences. This strategy aligns with the AIDA principle, where each piece of content is designed to attract attention, generate interest, cultivate desire, and encourage registration action. Additionally, using a cutting-edge approach thru creative visuals, short narratives, and authentic content strengthens the promotional appeal on digital platforms. Overall, this study concludes that the AFL promotional content has been strategically and innovatively crafted, enabling it to enhance the effectiveness of marketing communication and help strengthen audience engagement with the program.